Effects of fibromyalgia syndrome in patients with diffuse systemic sclerosis: Evaluation with 2010 American college of rheumatology criteria set - Ayse Ayan; Hanife Hale Hekim; Sebahat Yaprak Cetin (Indian Journal of Rheumatology)
Backgrounds: The aim of this study was to evaluate the frequency of fibromyalgia syndrome (FMS) according to the 2010 FMS criteria and to investigate its effects on quality of life in patients with diffuse systemic sclerosis (SSc). Methods: The study included 44 SSc patients with a mean age of 52.84 ± 13.35 years and 96 healthy adults with a mean age of 53.43 ± 14.67 years. The symptom severity scale, fibromyalgia impact questionnaire, beck depression and anxiety inventory, and the short form (SF)-36 were used for evaluations in the study. FMS was detected in 27 patients with SSc (62.79%) and 13 health controls (13.5%). Results: When SF-36 subscales were compared, a statistically significant difference was found in favor of the fibromyalgia patient group in respect of physical function, physical role difficulty, mental role, and pain scores (P: 0.04-0.00). Conclusion: Our results showed that FMS frequency was increased in patients with diffuse SSc and that FMS significantly affected the quality of life. In addition, the anxiety and depression levels were also increased in SSc patients with FMS. It can be recommended to assess patients with SSc for FMS during routine clinic examinations.